Laboratory implementation of X‐ray diffraction/scattering computed tomography. (1st February 2015) - Cersoy, Sophie; Leynaud, Olivier; Álvarez‐Murga, Michelle; Martinetto, Pauline; Bordet, Pierre; Boudet, Nathalie; Chalmin, Emilie; Castets, Géraldine; Hodeau, Jean Louis
<x xml:space="preserve">Abstract</x> This article demonstrates the possibility to perform X‐ray diffraction/scattering computed tomography experiments with a laboratory diffraction setup. This technique is useful to characterize samples with inhomogeneities on a length scale of a couple of hundred micrometres. Furthermore, the method can be applied to preliminary phase‐selective imaging prior to higher‐resolution characterization using synchrotron radiation. This article presents the results of test experiments carried out on a rhombohedral C60 sample previously studied at the ESRF.